2009
DOI: 10.1089/apc.2008.0181
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neuropsychological Functioning on Adherence to HAART in HIV-Infected Substance Abuse Patients

Abstract: This study assessed the frequency of neuropsychological impairment and its relationship to adherence in a sample of HIV-infected injection drug users (IDUs) in treatment. One hundred eight participants recruited between September 2006 and October 2008 completed psychodiagnostic and neuropsychological assessments and monitored HAART adherence over a 2-week period via the use of Medication Event Monitoring System (MEMS) electronic pill caps and self-report. Assessment of concurrent functioning included clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 59 publications
(59 reference statements)
0
23
0
Order By: Relevance
“…78 Further complicating the relationship between literacy and health, individuals with low literacy may also have overlapping cognitive deficits that further challenge medication adherence. 910 Although low literacy is only one facet in a constellation of poverty indicators, studies have shown low health literacy predicts poor health, including poor ART adherence, over and above other poverty indicators including lower education. 7,1112 For all of these reasons, it is imperative to focus on those with low health literacy in order to optimize access and adherence to ART to ultimately reduce HIV-related disparities.…”
mentioning
confidence: 99%
“…78 Further complicating the relationship between literacy and health, individuals with low literacy may also have overlapping cognitive deficits that further challenge medication adherence. 910 Although low literacy is only one facet in a constellation of poverty indicators, studies have shown low health literacy predicts poor health, including poor ART adherence, over and above other poverty indicators including lower education. 7,1112 For all of these reasons, it is imperative to focus on those with low health literacy in order to optimize access and adherence to ART to ultimately reduce HIV-related disparities.…”
mentioning
confidence: 99%
“…The inherent assumption in this approach is that it is the daily requirement for pills (and not the requirement to routinely attend clinic appointments), which serves as the main driver for low viral suppression rates. Examples of populations who could benefit from this prioritization scheme include adolescents [19], sex workers, or those suffering from mental illness [18,2123,25], substance abuse [16,24,43], and housing instability [44]. However, there are other characteristics of these populations that may make them less likely to benefit from long-acting agents, such as mobility and transience.…”
Section: Implementation Challengesmentioning
confidence: 99%
“…The benefits of ART are obviously dampened in those with inadequate adherence to treatment [13,14], and failure of HIV-positive individuals to take antiretrovirals as prescribed can lead to increased transmission within a community. Multiple factors are associated with reduced adherence in the developed and developing setting, including stigma [15,16], race/ethnicity [1720], depression [18,21,22], cognitive impairment [23], substance use [16,24], younger age [19,24,25], and adverse effects to medications [26]. Furthermore, rates of adherence to ART often decline over time [19,21,27,28], even when antiretrovirals are provided at no cost.…”
Section: Introductionmentioning
confidence: 99%
“…Applebaum et al [74] examined the frequency and severity of neuropsychological impairment of HIV-positive injection drug users, and the extent to which the impairment impacts antiretroviral adherence. They found neuropsychological impairment among HIV-infected individuals in substance abuse treatment to be exceptionally high (76%), with the overall mean as −1.51 (SD=1.20) across all neuropsychological tests.…”
Section: Adherencementioning
confidence: 99%